BIMBINGAN DAN PENYULUHAN TENTANG PENTINGNYA KEWIRAUSAHAAN BERBASIS MORAL ETIKA DAN MANAJEMEN KAS PADA JAMAAH MASJID ASY SYUHADA MALANG - Joko Samboro; Heru Utomo; Abdullah Helmy; Maskur Maskur; Musthofa Hadi (Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this service is to find the problems faced by the ASY SYUHADA congregation and congregation RT. 6 RW. 7 Sudimoro, Kel. Mojolangu, Kec. Lowokwaru Malang City and at the same time provide the right solution in order to achieve increased knowledge and capabilities in the operational field, especially in the field of entrepreneurship, namely starting before carrying out activities, with aspects of intention in entrepreneurship, then during activities, namely in terms of the importance of moral ethics in entrepreneurship and also given examples of the character of the Prophet Muhammad in trading, service quality and also selling techniques, which ended with an agreement or better known as a deal and marked by a handshake, so that work is not only profitable, but also gets blessings. Thus this activity can improve skills, both soft skills, especially in entrepreneurship and in cash managementThe methods used are: observation, to observe the activities carried out both in the economic and socio-religious fields, then interviews, explored to find problems and solutions that will be offered and simulations, to find the most suitable alternative in order to market goods more effectivelyThe findings are that guidance and training on: practical moral-ethical-based entrepreneurship and discussions about experience and how to manage cash well. well done